Identification And Characterization Of Pathogenic Microorganisms In The Health Environment - Harnia Harnia; Meillisa Carlen Mainassy; Glory Gelarich Simanjuntak; Rahmat Pannyiwi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Healthcare facilities have the potential to be reservoirs for various pathogenic microorganisms that can cause nosocomial infections. The presence of microorganisms on the surfaces of medical devices, treatment rooms, and ambient air can increase the risk of disease transmission to patients and healthcare workers. This study aims to identify and characterize pathogenic microorganisms found in healthcare environments. The study used a descriptive laboratory design with an observational approach. Samples were taken from treatment table surfaces, door handles, medical devices, and room air using swab and air sedimentation methods. Identification was carried out through culture examination, Gram staining, and biochemical tests. The results showed the presence of pathogenic bacterial isolates such as Staphylococcus aureus. aureus, Escherichia coli, and Pseudomonas aeruginosa. Some isolates showed resistance to certain antibiotics. It was concluded that healthcare environments have the potential to be a source of infection transmission, necessitating strict infection monitoring and control.